2021
DOI: 10.1016/j.ijid.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled open label trial on the use of favipiravir combined with inhaled interferon beta-1b in hospitalized patients with moderate to severe COVID-19 pneumonia

Abstract: To evaluate the therapeutic effectiveness of favipiravir combined with inhaled interferon beta-1b in adult patients hospitalized with moderate to severe COVID-19 pneumonia. Methods: A randomized, open-label controlled trial of oral favipiravir in adults hospitalized with moderate to severe COVID-19 pneumonia from June 22nd 2020 to August 13th 2020 was conducted. Patients were randomly assigned to receive either a combination of favipiravir with interferon beta-1b by inhalation aerosol or hydroxychloroquine (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 35 publications
0
85
1
5
Order By: Relevance
“…A total of 74 studies 2, 5, 15-18, 36-39, 41-44, 47-54, 56, 57, 59-63, 65-67, 69, 70, 72, 74-76, 78, 79, 82, 83, 85, 87, 88, 90-92, 94-97, 99, 100, 103-121, 125 including 48622 patients reported all-cause mortality. After filtering out treatments with small sample size following the specified criteria, the network included azithromycin, hydroxychloroquine, hydroxychloroquine plus azithromycin, colchicine, arbidol (umifenovir), favipiravir, remdesivir, lopinavir/ritonavir, convalescent plasma, methylprednisolone, dexamethasone, hydrocortisone, immunoglobulin, interferon beta, recombinant human granulocyte colony-stimulating factor (GCSF), tocilizumab, vitamin D 3 , baricitinib plus remdesivir, sulodexide and SOC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 74 studies 2, 5, 15-18, 36-39, 41-44, 47-54, 56, 57, 59-63, 65-67, 69, 70, 72, 74-76, 78, 79, 82, 83, 85, 87, 88, 90-92, 94-97, 99, 100, 103-121, 125 including 48622 patients reported all-cause mortality. After filtering out treatments with small sample size following the specified criteria, the network included azithromycin, hydroxychloroquine, hydroxychloroquine plus azithromycin, colchicine, arbidol (umifenovir), favipiravir, remdesivir, lopinavir/ritonavir, convalescent plasma, methylprednisolone, dexamethasone, hydrocortisone, immunoglobulin, interferon beta, recombinant human granulocyte colony-stimulating factor (GCSF), tocilizumab, vitamin D 3 , baricitinib plus remdesivir, sulodexide and SOC.…”
Section: Resultsmentioning
confidence: 99%
“…The hospital discharge rate was reported in 36 studies including 31436 patients and 19365 events. 2, 5, 15, 16, 36, 43, 47, 48, 50, 54, 60, 65, 66, 69, 75, 76, 79, 80, 83, 85, 88, 89, 91, 92, 96, 100, 103, 107-110, 112, 113, 116, 117, 120 Treatment nodes included in the network were azithromycin, hydroxychloroquine, hydroxychloroquine plus azithromycin, favipiravir, remdesivir, lopinavir/ritonavir, convalescent plasma, dexamethasone, interferon beta, tocilizumab, baricitinib plus remdesivir and SOC. Out of the 26 RCTs included in the NMA, nine were assessed as low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with the meta-analysis carried out by Shrestha et al 40 . Khamis et al also found intervention with favipiravir had no significant side effects, including hyperuricemia, abnormalities in liver enzymes, or QTc prolongation 42 .…”
Section: Discussionmentioning
confidence: 97%
“…Our analysis showed the need for admission in ICU is not statistically significant between the favipiravir groups and control groups. Khamis et al also revealed there was no significant difference between favipiravir and hydroxychloroquine group in the case of transfer to ICU 42 Additionally, Yan Lou et al found only two of the 22 patients in favipiravir and one patient in baloxavir marboxil group transferred to the ICU within seven days of starting intervention 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, fewer adverse events were observed in the favipiravir group than lopinavir/ritonavir group (Cai et al, 2020). On the contrary, the combination favipiravir and inhaled IFN beta-1b showed no difference for inflammatory biomarkers at hospital discharge and for the overall length of hospital stay when compared to hydroxychloroquine (Khamis et al, 2020). Another study, aiming to evaluate the clinical outcomes and plasma concentrations of baloxavir marboxil and favipiravir in COVID-19 patients, failed in demonstrating a virological effect and clinical benefits of these two drugs.…”
Section: Clinical Evidence Of Antiviral Agentsmentioning
confidence: 89%